Modulation of the Aβ peptide aggregation pathway by KP1019 limits Aβ-associated neurotoxicity. Issue 1 (12th November 2014) - Jones, Michael R.; Mu, Changhua; Wang, Michael C. P.; Webb, Michael I.; Walsby, Charles J.; Storr, Tim
Abstract : The Ru(iii ) complex KP1019 modulates the aggregation profile of the Alzheimer's Aβ peptide and limits Aβ toxicity in the SH-SY5Y cell line. Abstract : Alzheimer's disease (AD) is a neurodegenerative disorder that is increasing worldwide due to increased life expectancy. AD is characterized by two pathological hallmarks in the brain: amyloid-β (Aβ) plaque deposits and neurofibrillary tangles. A focus of AD research has concentrated on either inhibiting Aβ peptide aggregation that leads to plaque formation or breaking down pre-formed Aβ peptide aggregates. An alternative approach is to modulate the Aβ aggregation profile by facilitating the formation of Aβ species that are off-pathway and non-toxic. Herein, we report the re-purposing of the widely studied Ru(iii ) anti-cancer complex KP1019, towards regulating the aggregation profile of the Aβ peptide. Using electron paramagnetic resonance (EPR) spectroscopy, we conclude that KP1019 binds to histidine residues, located at the N-terminus of the peptide, in a rapid and robust fashion. Native gels and transmission electron microscopy (TEM) analyses have provided insight into the species and structures that are generated by KP1019-Aβ interactions. Finally, incubation in an in vitro human neuronal cell model has demonstrated that the formation of KP1019-Aβ species rescues cell viability from Aβ-associated neurotoxicity. Modulation of the Aβ aggregation pathway via covalent interactions with small molecules is thus a promising AD therapeutic strategy.